2011
DOI: 10.1074/jbc.m110.196790
|View full text |Cite
|
Sign up to set email alerts
|

NAD+-dependent SIRT1 Deacetylase Participates in Epigenetic Reprogramming during Endotoxin Tolerance

Abstract: Gene-selective epigenetic reprogramming and shifts in cellular bioenergetics develop when Toll-like receptors (TLR) recognize and respond to systemic life-threatening infections. Using a human monocyte cell model of endotoxin tolerance and human leukocytes from acute systemic inflammation with sepsis, we report that energy sensor sirtuin 1 (SIRT1) coordinates the epigenetic and bioenergy shifts. After TLR4 signaling, SIRT1 rapidly accumulated at the promoters of TNF-␣ and IL-1␤, but not IB␣; SIRT1 promoter bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
259
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 226 publications
(282 citation statements)
references
References 37 publications
18
259
0
5
Order By: Relevance
“…Yeung et al demonstrated that SIRT1-mediated deacetylation of Lys310 inhibits the transactivation of the RelA/p65 subunit and consequently suppresses NF-κB-dependent gene expression [39]. Liu et al reported that chronic inflammation stimulates the accumulation of SIRT1 in the promoter regions of cytokine genes and then induces deacetylation at the RelA/p65 subunit of the NF-κB complex [44]. Moreover, SIRT1-mediated deacetylation of NF-κB is crucially involved in the resolution of inflammation and metabolic disorders [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Yeung et al demonstrated that SIRT1-mediated deacetylation of Lys310 inhibits the transactivation of the RelA/p65 subunit and consequently suppresses NF-κB-dependent gene expression [39]. Liu et al reported that chronic inflammation stimulates the accumulation of SIRT1 in the promoter regions of cytokine genes and then induces deacetylation at the RelA/p65 subunit of the NF-κB complex [44]. Moreover, SIRT1-mediated deacetylation of NF-κB is crucially involved in the resolution of inflammation and metabolic disorders [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR-mRNA levels of human SIRT1, RELB, SIRT3 and murine Sirt1, Relb, Sirt3, and mitochondrial genes were measured by quantitative RT-PCR using gene-specific TaqMan primer/probe sets in an ABI prism 7000 sequence detection system (Applied Biosystems) as described (15). GAPDH mRNA was the internal loading control.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear SIRT1 and SIRT6 play a critical role in switching the initial inflammatory response to adaptation. In monocytes and neutrophils, this switch generates silent heterochromatin by inactivating NFB factor RelA/ p65 and activating NFB RELB transcription factor and other histone and DNA modifiers (2,(13)(14)(15)(16). Mechanistically, SIRT1 deacetylates lysine 310 of RelA/p65 and histone protein H1K27 and recruits RELB to promoters of target genes (15).…”
mentioning
confidence: 99%
See 2 more Smart Citations